2018
DOI: 10.3390/min8080341
|View full text |Cite
|
Sign up to set email alerts
|

Activation Mechanism of Lead Ions in Perovskite Flotation with Octyl Hydroxamic Acid Collector

Abstract: The activation mechanism of lead ions (Pb 2+ ) in perovskite flotation with an octyl hydroxamic acid collector was systematically investigated using microflotation experiments, zeta-potential measurements, adsorption tests, Fourier transform infrared (FT-IR) analysis, and X-ray photoelectron spectroscopy (XPS) analysis. The results of microflotation experiments and adsorption tests indicate that the presence of Pb 2+ can promote the adsorption of octyl hydroxamic acid (OHA) on the perovskite surface and enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In addition, the B-O bonding peak at 1510 cm À1 became stronger and the C-H bending vibration peak was shied from 1352 cm À1 to 1373 cm À1 with increasing borax concentrations, indicating that B-O-H or B-O-C bonding is promoted by the interaction between sodium borate and CH 3 . [25][26][27][28] Our previous study using proton nuclear magnetic resonance indicated that the presence of PMMA in the perovskite leads to the formation of hydrogen bonds between PMMA and the perovskite. 22 Specically, the interaction between the dipole moment of MA + (CH 3 NH 3 + ) in the perovskite and the polar C]O bond in PMMA promoted hydrogen bond formation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the B-O bonding peak at 1510 cm À1 became stronger and the C-H bending vibration peak was shied from 1352 cm À1 to 1373 cm À1 with increasing borax concentrations, indicating that B-O-H or B-O-C bonding is promoted by the interaction between sodium borate and CH 3 . [25][26][27][28] Our previous study using proton nuclear magnetic resonance indicated that the presence of PMMA in the perovskite leads to the formation of hydrogen bonds between PMMA and the perovskite. 22 Specically, the interaction between the dipole moment of MA + (CH 3 NH 3 + ) in the perovskite and the polar C]O bond in PMMA promoted hydrogen bond formation.…”
Section: Resultsmentioning
confidence: 99%
“…The procedure of estimating adsorption of a complexing flotation agent-capryl hydroxamic acid [12,13,19]-at the surface of perovskite before and after treatment by HPEMP and DBD included agitation of a mineral sample with the agent solutions, filtration of the solid phase, washing, drying of the filtrate and analysis of the mineral surface by the diffuse reflectance infrared Fourier Transform Spectroscopy (spectrometer IRAffinity, Shimadzy with accessory DiffuzIR, Pike Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Reduction in loss of TiO 2 (with perovskite during desli ming, washing and calcite flotation) in marketable concentrates is only achievable with direct selective flotation of perovskite in fresh water with agent IM-50, which ensures concentration of the useful component at the content of 48-50% and recovery of 80-83% from nonmagnetic ore fraction [5,12,13].…”
Section: Effect Of High-power Electromagnetic Pulses and Dielectric B...mentioning
confidence: 99%
“…To prepare Pt NPs supported on the highly porous LSTF-40, CeO 2 , and SiO 2 , each oxide powder was initially dispersed in 100 mL of water at pH 10. Modification with a basic solution was done to achieve a negative surface charge for the oxide. The porous CeO 2 support was synthesized by the calcination of cerium nitrate hexahydrate at 450 °C for 20 h in air. The specific surface area was 72.2 m 2 g –1 (Figure S1) and was similar to those of supports prepared by the wash-coating method in the literature. , For the SiO 2 support, we used a commercialized material (silicon (IV) oxide nanopowder, 80 nm ammonium persulfate (APS) powder).…”
Section: Methodsmentioning
confidence: 99%